Structural Analysis if Keroncong Song Arrangement Can’t Help Falling in Love Version of Line Entertaiment - Hendrianto, Dias Alrasyid; Handayani, Enie Wahyuning (PT. Hafasy Dwi Nawasena, 2024)
Keroncong songs are a form of traditional Indonesian music that has unique characteristics, while Line Music Entertainment is known for its modern arrangement style. This research aims to deeply analyze Line Music Entertainment's arrangement of the keroncong song “Can't Help Falling in Love”. The approach used in this research is descriptive analytical with a focus on data collection techniques through literature study and music analysis. The formulation of the problem in this research focuses on the arrangement of the musical form and structure of the keroncong song “Can't Help Falling in Love” by Line Music Entertainment. The results of the analysis show that Line Music Entertainment's version of the arrangement combines traditional keroncong elements with a distinctive modern touch, such as the use of varied musical instruments and a musical structure adapted to the characteristics of the original song. Changes in tempo, harmony, and vocal arrangement also affect the overall atmosphere of the music. The implication of this research is to provide new insights in understanding the process of keroncong song adaptation into the context of modern music. This research is also expected to contribute to the development of keroncong music arrangements in Indonesia, taking into account the creative and technical aspects applied by Line Music Entertainment.